Breeding, genetics, and genomics for tolerance against terminal heat in lentil: Current status and future directions. Issue 3 (24th March 2020) - Kumar, Jitendra; Sen Gupta, Debjyoti; Djalovic, Ivica
Abstract: Heat stress at terminal stage in lentil is one of the major factors causing drastic yield loss. Development of heat tolerant cultivars is one of the ways to tackle this problem. However, heat stress tolerance is a complex trait in nature and many morphological, physiological, biochemical, and metabolic changes are responsible for heat stress tolerance in lentil. Therefore, in the past years, efforts have been made to know genetics and genomics of heat stress tolerance in lentil. In this review, we discussed current progress on breeding, genetics, and genomics including quantitative trait locus (QTL) mapping, transcriptomics, proteomics, and network of metabolic pathways for heat tolerance and future directions for developing heat tolerant cultivars in lentil.